Anatomia ultraestrutural do nervo frênico de ratos: alterações decorrentes do diabete experimental crônico. - Rodrigues Filho, Omar Andrade (2008)
Streptozotocin (STZ) induced diabetes is known to cause a reduction of both conduction velocity and axon caliber in rat nerves and also a decrease in muscle fiber size. In the present study we investigated the phrenic nerve neuropathy, due to experimental diabetes induced by STZ and the evolution of this neuropathy in diabetic rats treated with insulin. Proximal and distal segments of the phrenic nerves were evaluated with the aid of a digital transmission electron microscope (TEM), from rats rendered diabetic, for 12 weeks, by injection of STZ. Control rats received vehicle. Treated rats received a single subcutaneous injection of insulin on a daily basis. Our results show that the phrenic nerves of diabetic rats present lesions of the myelinated and unmyelinated fibers, as well as the endoneural vessels and Schwann cells nuclei. The main alterations were the presence of axonal atrophy with loose myelin sheaths on the large caliber myelinated fiber. The small myelinated fibers presented signs of axonal atrophy or demyelination. Basement membrane thickening and signs of endothelial hyperplasia were present on the endoneural blood vessels of both diabetic groups but were more sever on the untreated animals. In the insulin treated animals, most of the alterations were seen on the small myelinated fibers and were related to demyelination signs. Unmyelinated fibers morphometry showed a larger number of fibers as well as larger average fiber area and diameter in both diabetic groups, compared to controls. Nevertheless, there was a reduction on the unmyelinated fibers percentage of occupancy and the ratio between myelinated and unmyelinated fiber numbers in both diabetic groups. No differences were found between both diabetic groups. In conclusion, the phrenic nerve is affected by the experimental diabetes and the conventional insulin treatment was not capable to prevent the small fiber neuropathy identified by TEM.